Impact of Hyperglycemia on Xerostomia and Salivary Composition and Flow Rate of Adolescents with Type 1 Diabetes Mellitus - Busato, Ivana Maria Saes; Machado, Maria Ângela Naval; Brancher, João Armando; Lima, Antônio Adilson Soares de; Deantoni, Carlos Cesar; Réa, Rosângela; Azevedo-Alanis, Luciana Reis (IntechOpen, 2011)
None